Edukasi Orang Tua Tentang Pendidikan Seks Pada Anak Usia Dini - Susanti, Siti Misra; Marwah, Marwah (Universitas Pahlawan Tuanku Tambusai, 2025)
The objective of this socialization is to provide an overview of the application of artificial intelligence in dealing with problems related to bullying. The positive effects of artificial intelligence on the life and growth of today's children will be widely utilized. At an early age, the protection of artificial intelligence is indispensable. It can play a role in preventing extreme behavior from developing in children. Post-bullying, the counseling program can be developed as part of parental counseling for their children's mental health. Additionally, an early warning function should be deployed, and permanent protection must be added to artificial intelligence. Among them, enhancing children's ability to judge, guide, and respond in events involving negative energy is essential. The results showed recent advancements in AI technology offer significant potential for more effective outcomes compared to traditional non-technological approaches in preventing and addressing children's bullying. These AI-driven solutions could potentially reduce the occurrence of bullying incidents, lessen their impact on children, and provide better protection for victims. Interactive video games that incorporate physical activities are now combining various elements such as muscle group engagement, body awareness, head-torso coordination, and social cooperation into comprehensive exercise packages. AI-enhanced video games can identify motivations behind bullying behavior in children by analyzing audio-visual data, assigning different levels of credibility to the information gathered during gameplay. These games are capable of providing immediate assistance when bullying attempts are detected, such as by playing calming music and animations, or by initiating mentoring sessions and discussions about appropriate behavior.